Analogijos vaidmuo latvių kalbos asmeninių įvardžių formų raidoje - Rosinas, Albertas (Baltistica, 1983)
The role of analogy in the evolution of form in Latvian personal pronouns In the article it is assumed that Latvian personal pronouns have inherited the “classical” case paradigm from the Lithuanian–Latvian parent language with a well-differentiated inflexion. The great variety of pronominal inflections in Latvian dialects and old manuscripts can be explained by the different conditions affecting the evolution of the language. Word-ending phonological and morphological changes, which created favourable conditions for the so-called changes by analogy, have resulted in morphological modifications in the system of all inflectional words. Therefore, the article is concerned with: (a) the process of neutralization of the singular accusative and instrumental cases in the (i̯) о and (i̯)ā-stem paradigms (which occurred after the above-mentioned phonological changes); (b) the effect of neutralization on identical cases of singular personal pronouns; (c) the effect of prepositions, which govern several cases, on the process of neutralization. The article also deals with the influence of the accusative-instrumental cases of singular pronouns on the modification of the plural pronominal paradigms, and with conditions and variants of the modification in question. On the basis of the data from Latvian dialects and old manuscripts a conclusion can be drawn that the modifications in the personal pronominal paradigms could have begun prior to the written language.